Efektivitas Intervensi Psikologi Positif “Flourish Through Futsal” terhadap Peningkatan Subjective Well-Being Pemain Futsal Dewasa Awal - Adel Yani Marliana; Dhea Ananda; Keysha Naiyna Aliffia; Muhammad Daffa Diyaul Haq; Muhamad Rafly (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Early-adult futsal players often face psychological pressure from performance demands, friction with teammates, and disappointment following defeat, which may lower their subjective well-being (SWB). This study aimed to examine the effectiveness of the “Flourish Through Futsal” positive psychology intervention program in improving SWB, life satisfaction, and positive affect, and in reducing negative affect, among five early-adult futsal players aged 18–25 years. The program consisted of four 60-minute sessions comprising psychoeducation, a Life Scoreboard activity, gratitude journaling, a character strengths exercise, and a best-possible-self exercise. Data were collected using the Satisfaction With Life Scale (SWLS) and the Scale of Positive and Negative Experience (SPANE), administered before (pre-test) and after (post-test) the program, and complemented by interviews and observation. Results showed that the mean life-satisfaction score increased from 16.6 to 24.4 and positive affect increased from 16.4 to 25.2, while negative affect decreased from 19.8 to 9.2 across all participants without exception. Qualitative findings further confirmed increased gratitude, self-confidence, and interpersonal closeness among participants. The structured positive psychology intervention proved effective in improving the short-term SWB of early-adult futsal players, warranting periodic implementation accompanied by long-term evaluation.